Lattice Oxygen Exchange Pathways in Nickel–Iron Metal–Organic Framework-Based Oxygen Evolution Electrocatalysts - Zheng, Daniel J.; McCormack, Kaylee; Peng, Jiayu; Garcia-Diez, Raul; Kataev, Elmar Yu; Schwarz, Fabian; Nehzati, Susan; Thyr, Jakob; Quevedo-Garzón, Wilson; Howchen, Benjamin; Bär, Marcus; Román-Leshkov, Yuriy; et al. (ACS Applied Materials and Interfaces, 2026)
The oxygen evolution reaction (OER) is crucial for electrofuel production. Metal–hydroxide organic frameworks (MHOFs), a subset of metal–organic frameworks with oxyhydroxide-like layers interconnected via organic linkers, have shown great promise as OER electrocatalysts. This study investigates lattice oxygen exchange in four Ni- and Fe-substituted MHOFs with varying linker stabilities using 18O isotope labeling combined with operando Raman spectroscopy. A negative correlation between 18O/16O lattice oxygen exchange and the OER activity is shown, with Fe ions further suppressing exchange. Operando X-ray spectroscopy (XAS) and UV–vis further reveals that lattice oxygen exchange primarily proceeds on reduced Ni2+ sites, with higher linker stability preserving more Ni2+ sites and promoting greater lattice oxygen exchange. Supported by density functional theory, the MHOF surface transforms into an OER-active MOxHy-like phase, explaining the negative correlation of lattice exchange with the OER activity. This work also identifies a noninnocent role of the Raman laser in inducing lattice oxygen exchange and offers critical insights into various lattice oxygen exchange pathways in MHOFs, demonstrating their distinction from the catalytic lattice oxygen evolution reaction mechanism.
CRIS-Team Scopus Importer:2026-01-23
Keywords: isotope labeling; lattice oxygen exchange; metal−organic frameworks; operando spectroscopy; oxygen evolution reaction